Winning in Brazil: how institutional voids affect the entry decision making process of foreign venture capital firms coming to Brazil - Albrecht, Christian (2015)
The master thesis for the achievement of the academic status master of science in international management (MPGI) will aim to solve the research question of how institutional voids affect the entry decision-making process of foreign venture capital firms coming to Brazil. This is a timely matter since in the past years there has been a sudden eruption of foreign VC involvement in Brazil. Based on the actionable framework by Khanna and Palpeu (2010) we conducted quantitative as well as qualitative research with two sets of interview partners in a two-phase analysis. We interviewed experts from VC firms, foreign VC firms based in Brazil and perspective VC firms that are looking to come to Brazil. We started with the former, derived lessons learned and analyzed how they affect the latter in reaching a decision. As we expected we found that depending on the industry that ventures are in, institutional voids can either pose an opportunity or a threat and hence attract or push away potential VC firms entering Brazil. Opportunities exist especially when exploiting institutional voids, for example through ventures in the marketplace efficiency. Threats are posed by investments in for instance hard infrastructure, where the economic, political and judicial systems as well as corruption and bureaucracy play demanding roles.